Judul Seroprevalensi Trichinellosis pada Ternak Babi di Wilayah Kabupaten Tangerang, Propinsi Banten (SEROPREVALENCE OF TRICHINELLOSIS IN PIGS IN THE TANGERANG DISTRICT PROVINCE OF BANTEN) - Setyani, Evie; Satrija, Fadjar; Sudarnika, Etih (Jurnal Veteriner, 2018)
Trichinellosis is a zoonotic disease caused by parasitic roundworms of the nematode class Trichinella spp, which is distributed worldwide. Indonesia is one of the countries with trichinellosis cases. This study aims to determine the seroprevalence of Trichinellosis in pigs in Tangerang Village, Banten Province. The sample size is determined with 95% confidence level, the expected prevalence is 5%, and the error rate is 5%. A total of 80 sera were collected from farm (27 sera) and from the sample banks of Disease Investigation Centre Subang (DIC Subang(53 sera)). The sample collection was examined serologically by the ELISA method for the examination of anti-Trichinella antibodies. The results showed that seroprevalence of trichinellosis in this study was 1.25% (confidence interval (CI) 95%; 0,22-6,75%). This case can be a threat to human health. Pigs that show seropositive results were the pigs with traditional husbandry practices with ground  flooring and without fences. The results of the questionnaires that distributed to the farmers indicated that all farmers did not know about trichinellosis, this may affect the presence of Trichinella in pigs.